ASPECTS CONCERNING SOME NUMERICAL METHODS FOR APPROXIMATE SOLUTION OF TWO-POINT BOUNDARY VALUE PROBLEMS - POP N., Daniel (Presa Universitară Clujeană, 2014)
The purpose of this work is to determinate the approximate solutions of boundary value problems with conditions inside the interval (0, 1) using collocation method with global B-spline functions of degree k (order k + 1), orthogonal polynomials Chebyshev and combined methods with B-spline functions or C.C method and Runge-Kutta methods.